Detection method for damaged layer on machined surface of yttrium oxide ceramic part
The method of inlaying, grinding, polishing, and scanning electron microscopy effectively addresses the challenge of detecting yttrium oxide ceramic damage layers, enhancing chip quality and yield.
Patent Information
- Application Number
- CN202411739512.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
AI Technical Summary
Current methods lack efficient and accurate non-chemical corrosion detection for surface damage layers in yttrium oxide ceramics, which affect chip quality and yield in high-density, high-energy plasma environments.
A method involving inlay treatment with polyurethane resin, followed by grinding, polishing, calcination, cleaning, and scanning electron microscopy to measure the depth and morphology of the damaged layer.
Accurately detects the damage layer, improving chip productivity and enabling precise observation of surface damage, suitable for yttrium oxide and other ceramics.
Smart Images

Figure CN119223218A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of detection, in particular to a method for detecting a damaged layer on the machining surface of an yttrium oxide ceramic part. Background Art
[0002] Advanced ceramic materials are products with excellent performance made from refined high-purity, ultra-fine inorganic compounds as raw materials and through advanced preparation technology. According to the material composition, advanced ceramics are mainly divided into oxide, nitride and carbide ceramics, etc.; and according to the purpose, they can be divided into two categories: structural ceramics and functional ceramics. Structural ceramics mainly have physical and chemical properties such as strong mechanical properties and corrosion resistance, while functional ceramics have electrical and magnetic properties. In the semiconductor industry, advanced ceramic materials, especially yttrium oxide ceramics, have become the preferred material for high process requirements due to their excellent plasma resistance. However, the processing of advanced ceramic materials is often accompanied by damage to the surface microstructure, forming a loose and soft layer, which will have a certain negative impact on chip production and processing, especially in a high-density, high-energy plasma environment. The particles of the damaged layer may be deposited on the wafer, seriously affecting the chip quality and yield.
[0003] Patent document CN115343301B discloses a method for characterizing the subsurface damage depth of non-metallic materials, which mainly includes: cutting, sample cleaning, vacuum drying, sample block embedding, grinding and polishing, selective etching, microscope observation and calculation, etc., which improves the accuracy and precision of the damage depth detection results. However, there are currently few reports in the prior art on non-chemical corrosion detection methods for ceramic material damage layers.
[0004] Therefore, how to provide an efficient and accurate method for detecting the surface damage layer of yttrium oxide ceramic parts is an industry-wide technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention innovatively proposes a method for testing the damaged layer of yttrium oxide ceramic parts processing, which aims to accurately measure the depth and morphology of the damaged layer, thereby improving chip productivity and performance.
[0006] The present invention provides a method for detecting a damaged layer on the machining surface of an yttrium oxide ceramic part, which mainly comprises: S1. Inlay treatment: cut the yttrium oxide ceramic piece into small pieces perpendicular to the processing direction, put the cut surface downward into a metallographic sample inlay machine, and use inlay powder for inlay treatment; S2. Grinding and polishing: The mounted sample is placed on an automatic metallographic sample grinding and polishing machine for grinding and then polishing; S3, calcination treatment: the sample after grinding and polishing is sintered in a sintering furnace; S4, cleaning treatment: the sample after calcination is firstly ultrasonically cleaned with an alcohol solvent, and then with pure water; then ultrasonically cleaned with an alcohol solvent, and then with pure water; S5. Drying: Dry the cleaned sample in an oven; S6. Damage layer detection: For the dried samples, use a scanning electron microscope to take pictures and measure the thickness of the damage layer.
[0007] As an implementable case, the size of the yttrium oxide ceramic piece is less than 20×20×10 mm.
[0008] As an implementable case, the inlay powder is polyurethane resin powder.
[0009] Furthermore, the polyurethane resin powder is of brand HSXQ-100, purchased from Suzhou Nanguang Electronic Technology Co., Ltd.
[0010] As an implementable case, the temperature of the inlay treatment is 130-150° C., and the insulation time is 5-10 minutes.
[0011] As is known to all, yttrium oxide ceramic parts will produce a damaged layer after processing. The purpose of the inlay treatment is to fix the observation surface of the sample and better observe the damaged layer. The sample is inlaid with polyurethane resin powder. The polyurethane resin can be cured at high temperature to form a fixed layer with high density. After the subsequent calcination treatment, the original processing damage of the ceramic surface can be better observed. However, the inlay temperature needs to be further limited. Too low a temperature will cause the polyurethane resin to fail to completely cure, and the surface density of the formed inlay layer will be low and the structure will be loose, which is not conducive to the subsequent grinding and polishing treatment; and the loose and incompletely cured resin is easy to absorb water and swell, and may even be unable to be inlaid and polished. Therefore, the preferred inlay treatment temperature of the present invention is 130-150°C to ensure that the polyurethane resin can be completely cured, which is convenient for the subsequent grinding and polishing treatment.
[0012] As an implementable example, in the grinding and polishing process, the rotation speed of the grinding disc used for grinding is 200-250rpm, and the grinding time is 20-60min.
[0013] Furthermore, the grinding disc is a diamond grinding disc with a mesh size of 80, purchased from Changsha Xinhui Electronic Technology Co., Ltd.
[0014] As an implementable example, in the grinding and polishing process, the rotation speed of the polishing disc used for polishing is 150-200 rpm, and the polishing time is 15-60 min.
[0015] Furthermore, the polishing disc is a polyurethane polishing disc with a Shore hardness of 70-80°, purchased from Changsha Xinhui Electronic Technology Co., Ltd.
[0016] The present invention can effectively eliminate the damage caused by processing through grinding and polishing, so as to more clearly observe the original damaged layer on the surface of the material; the present invention selects a suitable grinding and polishing tool, and first grinds and then polishes to ensure that the surface of the embedded fixing layer is smoother; however, the rotation speed of the grinding and polishing treatment should not be set too fast, otherwise it may cause further damage to the processed surface of the yttrium oxide ceramic part; of course, the rotation speed should not be set too slow. If the rotation speed is too slow, the processed surface layer is not completely removed, the damaged layer is covered, and the damaged layer cannot be well observed.
[0017] In the present invention, the polishing time is preferably 15-60 minutes, and the grinding time is 20-60 minutes; if the grinding and polishing time is too short, the machined surface layer is not completely removed, the damaged layer is covered by the machined surface layer, and the microscopic morphology of the damaged layer cannot be well observed.
[0018] As an implementable case, the starting temperature of the calcination treatment is 20-30°C, the heating rate is 0.5-2°C / min, and the sintering temperature is 600-800°C.
[0019] Further, when the sintering temperature reaches 300°C and 600°C, it is kept warm for 2-4 hours.
[0020] The calcination process step adopted in the present invention is mainly to completely sinter the polyurethane resin layer that has been ground and polished, so as to better observe the original damage layer of the yttrium oxide ceramic part. If it is not calcined or the calcination is incomplete, the polyurethane resin covers and is embedded in the surface of the damage layer, and the damage layer cannot be well observed.
[0021] At the same time, the inventors found that the heating rate and holding time during the calcination process also have a significant effect on the observation of the original processing damage layer. In the present invention, the preferred sintering heating rate is 0.5-2°C / min, and when the temperature reaches the sintering temperature of 300°C and 600°C, the insulation treatment is 2-6h; it can ensure that the polyurethane resin layer is completely sintered. If the heating rate is too fast and the insulation time is too short, the polyurethane resin may not be fully burned, and some residual resin adheres to the surface of the yttrium oxide ceramic sample, affecting the observation of the original processing damage layer.
[0022] As an implementable case, the alcohol solvent includes one of: methanol, ethanol, n-propanol, isopropanol, n-butanol, ethylene glycol, 1,2-propylene glycol, and glycerol.
[0023] As an implementable case, the ultrasonic power of the ultrasonic cleaning is 500-600W.
[0024] As an implementable case, the starting temperature of the drying treatment is 20-30°C, the heating rate is 1-3°C / min, the drying temperature is 100-120°C, and the drying insulation time is 1-2h.
[0025] Furthermore, the starting temperature of the drying process is room temperature 25°C, the heating rate is 2°C / min, the drying temperature is 105°C, and the drying insulation time is 1h.
[0026] Beneficial Effects (i) The present invention uses polyurethane resin powder to embed yttrium oxide ceramic samples. The polyurethane resin can be cured at high temperature to form a fixed layer with high density. After the subsequent calcination treatment, the processing damage of the ceramic surface can be better observed.
[0027] (ii) The present invention requires further limitation on the embedding temperature of the polyurethane resin powder. Too low a temperature will result in the polyurethane resin not being completely cured, which is not conducive to the subsequent grinding and polishing process. Therefore, the preferred embedding temperature is 130-150°C, which can ensure that the polyurethane resin is completely cured and facilitates the subsequent grinding and polishing process.
[0028] (III) In the present invention, the grinding and polishing treatment can effectively eliminate the influence of the machined surface layer of the yttrium oxide ceramic part on the machined damage layer, and the original machined damage layer on the surface of the yttrium oxide ceramic part can be observed more clearly, thereby improving the accuracy of the observation results.
[0029] (iv) The heating rate and holding time of the calcination treatment in the present invention also have a significant impact on the observation accuracy of the original processing damage layer. If the heating rate is too fast and the holding time is too short, the polyurethane resin cannot be fully burned, thereby affecting the accurate detection of the damage layer.
[0030] (V) The damage layer detection method provided by the present invention is simple and easy to operate, and can accurately test the depth and morphology of the damage layer. It is of great significance for optimizing the processing technology of yttrium oxide ceramic parts and improving chip productivity. At the same time, the damage layer detection method provided by the present invention is also suitable for the precise observation of damage layers in the processing of other oxide and nitride ceramic parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is a schematic diagram of the sample obtained after the inlay process in Example 1, and the black part is the polyurethane resin layer.
[0032] Figure 2 This is a schematic diagram of the sample obtained after grinding and polishing in Example 1, and the black part is the polyurethane resin layer.
[0033] Figure 3 This is a SEM schematic diagram obtained by detection in Example 1.
[0034] Figure 4 This is a SEM schematic diagram obtained by detection in Example 2.
[0035] Figure 5 This is a schematic diagram of the sample obtained after the inlay treatment in Comparative Example 1, and the black part is the polyurethane resin layer.
[0036] Figure 6 This is a schematic diagram of the sample obtained after grinding and polishing in Comparative Example 1, and the black part is the polyurethane resin layer.
[0037] Figure 7 This is a SEM schematic diagram obtained by detecting comparative example 2.
[0038] Figure 8 This is a SEM schematic diagram obtained by detecting comparative example 3.
[0039] Fig. 9 This is a SEM schematic diagram obtained by detecting comparative example 4.
[0040] Fig.10 This is a SEM schematic diagram obtained by detecting comparative example 5.
[0041] Fig.11 This is a SEM schematic diagram obtained by detecting comparative example 6.
[0042] Fig.12 This is a SEM schematic diagram obtained by detecting comparative example 7. DETAILED DESCRIPTION
[0043] In the following implementation cases: The metallographic specimen mounting machine used was purchased from Shanghai Metallographic Machinery Equipment Co., Ltd., model XQ-1.
[0044] The polyurethane resin powder used was purchased from Suzhou Nanguang Electronic Technology Co., Ltd., model HSXQ-100.
[0045] The automatic metallographic specimen grinding and polishing machine used was purchased from Shanghai Metallographic Machinery Equipment Co., Ltd., with the model number being YMPZ-2.
[0046] The grinding disc used was a diamond grinding disc with a mesh size of 80, purchased from Changsha Xinhui Electronic Technology Co., Ltd.
[0047] The polishing disc used was a polyurethane polishing disc with a Shore hardness of 70-80°, purchased from Changsha Xinhui Electronic Technology Co., Ltd.
[0048] The sintering furnace used was a high temperature experimental electric furnace purchased from Alsay (Suzhou) Inorganic Materials Co., Ltd., model SX-18-222820.
[0049] The equipment used for the ultrasonic cleaning is a WeiNeng ultrasonic cleaning instrument purchased from Suzhou Chuanghui Electronics Co., Ltd., model number CH-10BW.
[0050] The oven used was an electric blast drying oven purchased from Bangsi Instrument Technology (Shanghai) Co., Ltd., model 101-00BS.
[0051] The scanning electron microscope used was purchased from Zeiss Group, model SIGMA300.
[0052] Example 1 The present example provides a method for detecting a damaged layer on the machining surface of an yttrium oxide ceramic part, including: S1. Inlay treatment: cut the yttrium oxide ceramic piece into small pieces perpendicular to the processing direction, with a size less than 20×20×10 mm, with the cut surface facing downward, and put it into a metallographic sample inlay machine. Use polyurethane resin powder for inlay treatment. The inlay temperature is 140°C and the holding time is 5 minutes. S2. Grinding and polishing: The mounted sample is placed on an automatic metallographic sample grinding and polishing machine and first ground with a grinding disc at a grinding speed of 220 rpm for 30 min; then polished with a polishing disc at a polishing speed of 200 rpm for 30 min; S3, calcination treatment: the sample after grinding and polishing treatment is sintered in a sintering furnace, the sintering starting temperature is room temperature 25 ° C, the heating rate is 0.5 ° C / min, and the sintering temperature is 600 ° C; when the sintering temperature reaches 300 ° C and 600 ° C, keep warm for 3 hours respectively; S4, cleaning treatment: the sample after calcination treatment is first ultrasonically cleaned with methanol for 20 minutes, then with pure water for 20 minutes; then with isopropanol for 20 minutes, and then with pure water for 20 minutes; the power of ultrasonic cleaning is 600W; S5. Drying treatment: The cleaned samples are dried in an oven. The starting temperature of the drying treatment is 25°C, the heating rate is 2°C / min, the drying temperature is 105°C, and the drying holding time is 1h. S6. Damage layer detection: For the dried samples, use a scanning electron microscope to take pictures and measure the thickness of the damage layer.
[0053] In this example, the sample obtained after the mounting process is as follows Figure 1 shown.
[0054] In this example, the sample obtained after grinding and polishing is as follows Figure 2 shown.
[0055] The SEM (scanning electron microscope) inspection diagram in this example is as follows Figure 3 As shown, from Figure 3 It can be clearly seen that the thickness of the damaged layer is 12.34-15.34μm.
[0056] Example 2 The present example provides a method for detecting a damaged layer on the machining surface of an yttrium oxide ceramic part, including: S1. Inlay treatment: cut the yttrium oxide ceramic piece into small pieces perpendicular to the processing direction, with a size less than 20×20×10 mm, with the cut surface facing downward, and put it into a metallographic sample inlay machine. Use polyurethane resin powder for inlay treatment. The inlay temperature is 140°C and the holding time is 5 minutes. S2. Grinding and polishing: The mounted sample is placed on an automatic metallographic sample grinding and polishing machine and first ground with a grinding disc at a grinding speed of 220 rpm for 40 min; then polished with a polishing disc at a polishing speed of 200 rpm for 20 min; S3, calcination treatment: the sample after grinding and polishing is sintered in a sintering furnace, the starting sintering temperature is room temperature 25 ° C, the heating rate is 1 ° C / min, and the sintering temperature is 600 ° C; when the sintering temperature reaches 300 ° C, keep it warm for 3 hours; when the sintering temperature reaches 600 ° C, keep it warm for 2 hours; S4, cleaning treatment: the sample after calcination treatment is first ultrasonically cleaned with methanol for 20 minutes, then with pure water for 20 minutes; then with isopropanol for 20 minutes, and then with pure water for 20 minutes; the power of ultrasonic cleaning is 600W; S5. Drying treatment: The cleaned samples are dried in an oven. The starting temperature of the drying treatment is 25°C, the heating rate is 2°C / min, the drying temperature is 105°C, and the drying holding time is 1h. S6. Damage layer detection: For the dried samples, use a scanning electron microscope to take pictures and measure the thickness of the damage layer.
[0057] The SEM detection schematic diagram obtained in this example is as follows Figure 4 As shown, from Figure 4 It can be clearly seen that the thickness of the damaged layer is 8.897-10.52μm.
[0058] Comparative Example 1 The specific implementation of this example is the same as that of Example 1, except that the embedding temperature in the embedding process is 120°C.
[0059] In this example, the sample obtained after the mounting process is as follows Figure 5 shown.
[0060] In this example, the sample obtained after grinding and polishing is as follows Figure 6 shown.
[0061] In this example, the embedding temperature is 120°C, at which time the polyurethane resin is not completely cured and has a loose structure, making it impossible to embed and polish.
[0062] Comparative Example 2 The specific implementation of this example is the same as that of Example 1, except that the grinding speed is 120 rpm, the grinding time is 20 min, the polishing speed is 100 rpm, and the polishing time is 20 min.
[0063] The SEM detection schematic diagram obtained in this example is as follows Figure 7 shown.
[0064] In this case, since the rotation speed of the polishing and grinding process was too slow, the processed surface layer was not completely removed, and the damaged layer was covered and could not be well observed.
[0065] Comparative Example 3 The specific implementation of this example is the same as that of Example 1, except that the grinding speed is 220 rpm, the grinding time is 10 min, and the polishing speed is 200 rpm, and the polishing time is 10 min.
[0066] The SEM detection schematic diagram obtained in this example is as follows Figure 8 shown.
[0067] In this case, since the polishing and grinding time was too short, the processed surface layer was not completely removed, the damaged layer was covered and could not be well observed.
[0068] Comparative Example 4 The specific implementation of this example is the same as that of Example 1, except that the object of the inlay process is an unprocessed yttrium oxide ceramic part.
[0069] The SEM detection schematic diagram obtained in this example is as follows Fig. 9 shown.
[0070] In this example, since the test object is an unprocessed yttria ceramic part, there is no damaged layer and it cannot be observed.
[0071] Comparative Example 5 The specific implementation method of this example is the same as that of Example 1, except that this example does not include the inlay process and the calcination process, that is, after the yttrium oxide ceramic part is cut, the cleaning step is directly performed, and then the drying step is performed, and then the damage layer detection is performed.
[0072] The SEM detection schematic diagram obtained in this example is as follows Fig.10 shown.
[0073] In this example, since the yttrium oxide ceramic part has not been subjected to inlay treatment or calcination treatment, it is impossible to distinguish between the damaged layer and the processed layer.
[0074] Comparative Example 6 The specific implementation of this example is the same as that of Example 1, except that the calcination process is not included.
[0075] The SEM detection schematic diagram obtained in this example is as follows Fig.11 shown.
[0076] In this case, the yttrium oxide ceramic part has not been calcined, and the polyurethane resin is covered and embedded on the surface of the damaged layer, so the damaged layer cannot be well observed.
[0077] Comparative Example 7 The specific implementation of this example is the same as that of Example 1, except that the heating rate during the sintering process is 10° C. / min, and when the sintering temperature reaches 300° C. and 600° C., each is kept warm for 1 hour.
[0078] The SEM detection schematic diagram obtained in this example is as follows Fig.12 shown.
[0079] In this case, since the heating rate was too fast and the holding time was too short during the calcination process, the polyurethane resin could not be fully burned and adhered to the surface of the yttrium oxide ceramic sample, affecting the observation of the damaged layer.
Claims
1. A method for detecting a damaged layer on the machining surface of an yttrium oxide ceramic part, characterized in that: include: S1. Inlay treatment: cut the yttrium oxide ceramic piece into small pieces perpendicular to the processing direction, put the cut surface downward into a metallographic sample inlay machine, and use inlay powder for inlay treatment; S2. Grinding and polishing: The mounted sample is placed on an automatic metallographic sample grinding and polishing machine for grinding and then polishing; S3, calcination treatment: the sample after grinding and polishing is sintered in a sintering furnace; S4, cleaning treatment: the sample after calcination is firstly ultrasonically cleaned with an alcohol solvent, and then with pure water; then ultrasonically cleaned with an alcohol solvent, and then with pure water; S5. Drying: Dry the cleaned sample in an oven; S6. Damage layer detection: For the dried samples, use a scanning electron microscope to take pictures and measure the thickness of the damage layer.
2. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: The inlay powder is polyurethane resin powder.
3. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: The temperature of the inlay treatment is 130-150° C., and the insulation time is 5-10 minutes.
4. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: In the grinding and polishing process, the polishing disc used for polishing has a rotation speed of 150-200 rpm and the polishing time is 15-60 min.
5. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: In the grinding and polishing process, the rotation speed of the grinding disc used for grinding is 200-250rpm, and the grinding time is 20-60min.
6. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to any one of claims 1 to 5, characterized in that: The starting temperature of the calcination treatment is 20-30°C, the heating rate is 0.5-2°C / min, and the sintering temperature is 600-800°C.
7. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 6, characterized in that: In the calcination process, when the sintering temperature reaches 300°C and 600°C, it is kept warm for 2-4 hours.
8. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: The alcohol solvent includes one of methanol, ethanol, n-propanol, isopropanol, n-butanol, ethylene glycol, 1,2-propylene glycol and glycerol.
9. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: The ultrasonic power of the ultrasonic cleaning is 500-600W.
10. The method for detecting the damaged layer on the machining surface of yttrium oxide ceramic parts according to claim 1, characterized in that: The starting temperature of the drying treatment is 20-30°C, the heating rate is 1-3°C / min, the drying temperature is 100-120°C, and the drying insulation time is 1-2h.
Citation Information
Patent Citations
Method for producing exhaust pipe
CN102678248A
Production method of polycrystalline transparent ceramics for electronic products
CN104844270A
Engineering ceramic grinding damage detection method based on illumination intensity
CN107664641A
Subsurface damage detection method based on metallographic inlaying
CN112834304A
Characterization method for subsurface damage depth of non-metallic material
CN115343301A